Study the effect of relationship marketing of the future consumer behavioral intention to use the company service: GIG Technology Holdings Sdn Bhd / Fara Elani Mohd Saufi - Mohd Saufi, Fara Elani (Faculty of Business Management, 2009)
This research is investigates a possible “Effect of Relationship Marketing of the Future Consumer Behavioral Intention to Use the GIG Technology Holdings Sdn Bhd Services”. The main objective is to determine the effect of the relationship marketing toward the future consumer behavioral intention to use the GIG Technology Holdings Sdn Bhd. Then researcher is determining the distribution between relationship marketing and consumer behavioral intention. Lastly, objective is to find the alternatives to improve relationship marketing towards to the GIG Technology Holdings Sdn Bhd. All objectives are consisting of four kinds of relationship marketing those are Trust, Commitment, Retention and Loyalty. About 25 respondents were getting from the research to help for accomplish this research by answering questionnaires had been distributed to them. This research was been used the probability sampling techniques and simple random techniques to get the data that are required. The finding showed questions in every each of relationship must highlight and recommend the company to create a consumer behavioral intention towards to their consumer. In the result, it determines the significant of the loyalty are shows the relationship between GIG Technology Holdings Sdn bhd and the government are more into helping in a sense that they are bumiputra.